(3eNJda GdTjYI aj CMcGe GdTQjYIs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg eMb GdMb heXgQg (B... (3cJGH GdWgGQI HGH GdejGg hCMcGegG hajg aUhd GdChd aj GdeGA Gdbdjd, eSCdI GJab YdeGDfG EdG GHf Ybjd Ydi Cf GdeGAs
(3BNQgG (B:s
(3BNQgG(B: (3hCMeO Hf eMeO Hf CHj fUQ bGd(B: (3PcQfG dg GdchaI heG hVY YdjgG ef GdNQGL heG SGQ ajgG Cgd HjJg abGd GSde WhYG JQcJ jOg CNP efg GdYTQ eeG SbJ GdeGA hGdCfgGQ hfUas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 227s
(3GdPQjYI, L (B20: 145s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis